Development of Android apps for matrix operations - Ang, Felicia Xiang Ying (Nanyang Technological University, 2023)
Matrix operations have a wide range of applications in the world such as Circuit Analysis and Electromagnetics. Although there have been already a few support such as MATLAB to perform matrix operation computations, there is still not enough support for the mobile aspect. As such, this project aims to develop an Android application for matrix operations. The application would allow the users to perform matrix operation computations and the step-by-step solutions would be displayed on the screen. The testing would be done via the Pixel 3 API 29 (android-x86 emulator) and the SM P610 (android-arm64) device. The correctness of the results produced by the application is confirmed by MATLAB. This report will present the introduction, literature review, implementation, user interface, testing, case study, conclusion, future work as well as the learning outcome and reflection.